High potential microbial denitrification in non-hypoxic intermediate waters of the South China Sea basin - Zeng, Jian; Chen, Baohong; Shi, Guozong; Guan, Yanyun; Zhuo, Zesheng (Frontiers in Marine Science, 2025)
IntroductionThe discovery of microbial denitrification in non-extreme oxygen-deficient environments has drawn growing attention. At the same time, it is reshaping previous understanding of the spatial pattern of marine nitrogen (N) sinks. The non-hypoxic subsurface and intermediate waters of the South China Sea (SCS) basin possess potential favorable conditions for the occurrence of microbial denitrification, which are long-term overlooked and remained unexplored.MethodsMethods: In this study, a series of 15N-isotope tracers incubation experiments, combined with functional genes characterizations and hydro-chemical parameters analysis, were conducted during cruise. Rigorous statistical analysis was performed to reveal the correlations between environmental variables and denitrifying activity.ResultsIt showed that representative denitrification functional genes (narG and nirS) are ubiquitously presented at moderate abundances (0.1×104 12×105 copies/L) across the water columns. In the intermediate waters (600 1500 m) with low dissolved oxygen (DO) saturation (20% 30%), weak in situ denitrification rates (0.2 1.1 nmol N2/L/d) were detected. However, under simulated anoxic conditions, active denitrification was detected in most sampling layers, with potential rates (0.2 33 nmol N2/L/d) comparable to those in typical oxygen-deficient zones (ODZs).DiscussionSignificant correlations between suspended particulate matter (SPM) and particulate organic carbon (POC), contents with both denitrification rates and functional gene abundances were observed. It is inferred that low ambient DO levels, as well as hypoxic micro-niches in particulate matter, may together drive denitrification occurrence in the basin waters. Besides, particulate matter plays a critical role in influencing metabolic activity and spatial variability of denitrification in the basin. Since the mid-water of the SCS basin sustains a large particulate loading from terrestrial input and hydrodynamics, it is likely to maintain strong denitrification potential in the water body. We further propose a preliminary framework of coupling between particle transport driven by complex environmental dynamics and microbial N removal. Our study not only provides a potential implication for the need to re-evaluate the N budgets in the SCS basin, but also offers a new perspective of mechanism interpretation for microbial N removal in non-hypoxic marine environments.